CHILDHOOD LICHEN PLANUS: A STUDY OF 54 CASES FROM PAKISTAN - Habib, Aamir; Aamir, Reham Binte; Shahzad, Sohail (Journal of Ayub Medical College Abbottabad, 2024)
Background: To determine the clinical profile of Childhood Lichen Planus (LP) in Pakistani patients presenting to Dermatology outdoors of a Tertiary Care Hospital. It was a cross-sectional study, conducted at the Dermatology Outpatient of a Tertiary Care Hospital in Pakistan from December 2021 to December 2023. Methods: All new patients with either gender up to the age of 15 years with clinical diagnosis of LP were included. Clinical data was recorded for each patient separately. Physical examination was performed to determine the type of disease, presence or absence of Koebner phenomenon and the presence of other associated diseases. The data collected was analyzed using Statistical Package for Social Sciences (SPSS) version 23. Results: The mean age of onset was 9.792±2.774 and mean duration was 11.63±6.83 months. Pruritus was found in 51 (94.4%) patients. Classic LP was found in 35 (64.9%) cases, hypertrophic LP was found in seven (13.0%) cases and linear LP was found in six (11.1%) patients. Lichen planopilaris, actinic lichen planus and atrophic lichen planus were seen in one (1.9%) patient each. Nail involvement was seen in 5 (9.3%) patients with only one (1.9%) having nail only lichen planus. Similarly, mucosal involvement was seen in 7 (13.0%) patients and only two (3.7%) patients had mucosal only lichen planus. Conclusion: Lichen planus is uncommon in children. Childhood LP largely resembles adult LP. There is no significant gender predominance. Nail Lichen planus and mucosal LP are rare and family history and associated systemic diseases are found very rarely.